Spectrum Lighting During Pullet Rearing and Its Impact on Subsequent Production Performance in Layers. (16th September 2019) - Takeshima, K; Hanlon, C; Sparling, B; Korver, D R; Bédécarrats, G Y
SUMMARY: Artificial lighting is used to control growth and reproduction. Lighting protocols are defined by the quantity (photoperiod, intensity) and the quality (wavelength) of light. Recently, with the introduction of light emitting diode (LED) bulbs, interest has grown in investigating the effect of spectrum lighting. Thus, the aim of this study was to examine the effect of red and green light on growth during pullet rearing, and on possible carry-over effects during the subsequent adult phase. Lohmann Brown-Lite chicks were raised in a 2-story free run barn divided into 4 sections and exposed to either 60% red LED (RL) or 60% green LED (GL) light treatments. At 19 wk, all birds were moved to an adult free-run barn with RL and GL pullets placed on separate halves of the barn. In the adult barn, all birds were exposed to RL. Body weight, egg production, ovarian morphology, estradiol and calcium levels, as well as bone structure were recorded until 70 wk. Although no consistent significant difference was observed in body weight or general reproductive parameters, RL pullets tended to sexually mature earlier. As well, no carry-over effect was detected. Regardless of pullet treatment, egg production remained high throughout, especially towards the end of lay. In conclusion, spectrum lighting during the rearing of layer pullets did not impact growth or subsequent production performance; however, exposing adult hens to RL may be beneficial to maintain high egg production.